Faktor Risiko yang Berhubungan dengan Perilaku Pencegahan DM Tipe 2 Berdasarkan Teori Health Belief Model pada Remaja - Aisyhabilla Oktaviani; Munaya Fauziah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Type 2 diabetes mellitus (T2DM), once primarily affecting adults, is now increasingly prevalent among adolescents due to lifestyle changes. Adolescents represent a critical age group for the development of healthy behaviors, making it essential to identify factors influencing T2DM preventive behavior. This study employed a quantitative approach with a cross-sectional design, conducted in Ciledug District, Tangerang City, from April to June 2025. A total of 224 adolescents aged 15–24 years were selected using stratified random sampling. Data were analyzed using the Chi-Square test. The results showed that 49.1% of adolescents exhibited poor preventive behavior against T2DM. Gender and perceived barriers were significantly associated with preventive behavior (p < 0.05), whereas other factors such as age, family history, and other Health Belief Model (HBM) constructs were not significantly related. In conclusion, adolescents’ preventive behavior toward T2DM remains relatively low and is influenced by perceived barriers. Therefore, interventions should focus on reducing perceived barriers while enhancing environmental support and self-motivation. Active involvement from schools, governments, families, and communities is crucial to foster positive behavioral change.